Simple multi atribut rating technique methods in a decision making for the best employees - Suwaebatul Aslamiyah; Eko Yulianto; Mahmud Safudin (Institute of Computer Science (IOCS), 2023)
Providing periodic rewards to employees with the best qualities has several functions, including strengthening employee motivation to achieve achievements and also retaining employees from being targeted by other organizations. A good and attractive reward system can minimize the number of employees leaving. The weakness that is generally found in the best employee assessment system is the accuracy of the calculation results and the unavoidable nature of the subjectivity of the assessment team. The aim of this research is to implement the Simple Multi Attribute Rating Technique (SMART) method in minimizing the weaknesses of the best employee assessment system that is already running. The result of this research is a calculation system for assessing the best employees